Inovasi Pelayanan Publik Berbasis E-GOV Studi Kasus Aplikasi Tangerang Live, Dinas Komunikasi dan Informatika Kota Tangerang - Rosita, Suswilya Dwicahya; Nurpatonah, Sipa; Febrianti, Andin; Makarim, Muhammad Hazmi Mamduh; Prasetyo, Eko (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The "Tangerang Live" application presents a public service innovation that provides practical solutions for the residents of Tangerang City. This application is an example of how technology can assist in optimising effective and efficient public services. The "Tangerang Live" application has the advantage of providing practical solutions for residents seeking information or services. In the context of e-gov, the use of an application like this can be considered as an example of e-government implementation that facilitates access to information and services for the community. the use of this application can also help in realising the concept of public services that are more transparent, accountable and responsive. This is in line with the theory put forward by Lenvinne et al (2011) related to the elements of public service quality, such as Responsiveness, Responsibility, and Accountability. The method used in this research is qualitative method by conducting interviews with related agencies, observation, documentation and literature study. The advantage of the "Tangerang Live" application is that it can facilitate the parties involved in the service process, such as government agencies and the community, to connect and collaborate in providing effective and efficient public services.